ENDOPROSTHESIS AND ARTHRODESIS OF THE ANKLE JOINT. COMPARISON OF TREATMENT OUTCOMES - D. L. Miroshnikov; O. V. Sabodashevskiy; A. A. Afaunov; I. I. Zamyatin; H. H. Matar; Y. V. Napakh (Инновационная медицина Кубани, 2019)
Background. Study long-term results following endoprosthesis and arthrodesis of an ankle joint.Material and Methods. During the period from 2006 to 2018, we arthrodesed 102 ankle joint and endoprosthesing with DePyu Mobility implants in patients with arthroses of various etiology. Of operated on patients,there were 16 female patients (61.5%) and 10 (38.5%) male patients, age range was from 19 to 78 years (mean age 50.6 years). The average operative time was 1.6 hours. Average blood loss was 200 ml. Of patients with arthrodesis procedures: 76 (75.5%) – female patients and 26 (25.5%) – male patients, age range varied from 32 to 68 years (mean age was 49 years). The average operative time was 2 hours, and average blood lost was 300 ml. Results. To compare surgical results we applied AOFAS score defining treatment results according to functional criteria. Of 31 cases with endoprosthesing in 29 (93.5%) we observed sufficient long term results, and in 2 cases (6.5%) – satisfactory. Twenty-five patients (80.6%) were pleased with outcomes of surgery. In 20 patients (64.5%) volume of movement is less than usual, but more comparing to preoperative value. In 3 cases (9.3%) the pain syndrome was also stopped and volume of movements was unchanged and in 3 patients movements were normal (they had no significant ristrictions prior to the operation). In 1 case (3.2%) after endoprosthesing of ankle joint we observed varus deformity at the level of subtalar joint, so we performed correcting subtalar arthrodesis. In 2 patients (6.4%) achieved results were assessed as insufficient due to forming femoroacetabular impingement and pain syndrome. Cases of unstable endoprostheses were not seen. Following ankle joint arthrodesis we observed sufficient long-term results in 78 patients (76.4%), satisfactory results were in 24 (23.5%) patients. And in 24 cases (23.9%) patients required reoperation due to poor results of arthrodesis.Conclusion. Ankle joint replacement with modern implants allows to achieve sufficient clinical results and it is a hi-tech alternative to arthrodesis procedures.